Mulheres protagonistas em uma igreja machista: pesquisa sobre a “Rede Um Grito Pela Vida” na missão de libertar corpos - Silva, Luzemilca dos Santos (2024)
This paper analyzes the feminist movements in the Catholic Church, especially the organization “Rede Um Grito Pela Vida” (A Cry for Life Network). Using Laurence Bardin's content analysis, it investigates women's protagonism in a sexist environment and how feminist movement contributes to the social and religious emancipation of women in the field of Religious Sciences. It explores the historical gender discrimination and violence sustained by Judeo-Christian patriarchal culture, highlighting how religion can legitimize the oppression of women. It shows how, despite the social view of religious women as submissive, feminist movements within churches highlight the possibility of understanding and challenging the power exercised by the religious system. Feminist women reinterpret religious discourse, using experiences of violence and discrimination to reclaim their true identity, freeing themselves from ideologies that have kept them subjugated in all spheres.